Pengaruh literasi keuangan, financial capital, kebijakan pemerintah terhadap kinerja usaha pada usaha kecil dan menengah di Jawa Timur - Dyah Regita Pramestiningrum; Rr. Iramani (Journal of Business & Banking, 2019)
SMEs contribute greatly to economic growth in Indonesia, SMEs are able to produce GDP up to 59.08% (Bank Indonesia dan LPPI, 2015). The purpose of this study to determine the effect of financial literacy of SME managers, financial capital of SME and government policies on SME’s business performance. Total samples in this study are 177 SMEs. The sample data of this study are primary data in the metropolitan cluster in East Java which includes Surabaya, Gresik, Sidoarjo and Mojokerto. The results of this study indicate that the ability of SMEs managers about debt literacy has significantly and negative effect to business performance, the ability of SMEs managers about book keeping literacy and budgeting literacy have significantly and positive effect to business perfomance. Financial capital has significantly and positive effect to business performance and government policy in SMEs metropolitan cluster has no affect on the SMEs business performance.